2008
DOI: 10.1002/app.28250
|View full text |Cite
|
Sign up to set email alerts
|

Influence of some additives on the performance of wood flour/polyolefin composites

Abstract: ABSTRACT:The main objective of this study was to investigate the effect of different additives, namely, maleic anhydride, alumina trihydrate (ATH), and a mixture of both on wood flour/polyolefin (50/50) composite samples. The polyolefins used were polyethylene (PE), polypropylene (PP), and a mixture of both PE and PP (50/50 w/w). The effects were studied in terms of the percentage water absorption, volumetric swelling efficiency, and mechanical and electrical properties. We found that the absorption of water a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The decline in flexural properties may be attributable to the aggregation of the woody materials. Poor interfacial adhesion leads to composites with poor mechanical properties [27,[31][32][33]. Reports by Lee et al [2,34] demonstrated that the MOR and MOE of various WPCs were in the range of 8.5-25.3 MPa and 1.0-2.4 GPa, respectively; even the flexural properties of BFRPC with 80 wt% bamboo fiber were higher than those of conventional WPCs.…”
Section: Resultsmentioning
confidence: 90%
“…The decline in flexural properties may be attributable to the aggregation of the woody materials. Poor interfacial adhesion leads to composites with poor mechanical properties [27,[31][32][33]. Reports by Lee et al [2,34] demonstrated that the MOR and MOE of various WPCs were in the range of 8.5-25.3 MPa and 1.0-2.4 GPa, respectively; even the flexural properties of BFRPC with 80 wt% bamboo fiber were higher than those of conventional WPCs.…”
Section: Resultsmentioning
confidence: 90%
“…With the increase of the WF content, the MFI of the composites gradually decreased from 0.4 to 0.33 g/10 min. On one hand, the added MAH-g-PP could not only form ester bonds with WF, but also form physical interlocks with PP molecular chains, which resulted in the decreased flowability of the composites [21][22][23][24]. On the other hand, the excessive addition of WF could also result in the internal friction between WF particles.…”
Section: Resultsmentioning
confidence: 99%
“…The polyethylene end can penetrate into and entangle with HDPE chains thereby forming physical interlocks. 17,36,37…”
Section: Resultsmentioning
confidence: 99%
“…Many technical issues regarding WPCs have been well studied, for example, measurement and analysis of impact fracture and deformation behavior, as well as the influence of various additives on mechanical properties, aging, and durability. 17 22 The melt rheology, although critical for many processing issues, is poorly understood. Rheological properties similar to other suspensions of polymeric matrices 16,23 are anticipated for WPCs.…”
Section: Introductionmentioning
confidence: 99%